1996
DOI: 10.1111/j.1432-1033.1996.0064t.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin mRNAs in Schistosoma Mansoni do not have Iron‐Responsive Elements for Post‐Transcriptional Regulation

Abstract: Schistosomu mansoni possesses two isoforms of ferritin, soma and yolk ferritin. The soma ferritin occurs at a low level in most cells of both genders, whereas the yolk ferritin is a female-specific gene product that is expressed at high level in the vitellarium. In higher animals, ferritin mRNA is regulated by iron via the interaction of cytoplasmic binding proteins (IRPs) with a specific sequence element in the 5' untranslated region (UTR) referred to as the iron-responsive element (IRE). Sequence studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…The only metazoan species where we failed to identify an IRE were Caenorhabditis elegans and Schistosoma mansoni, consistent with previous observations (Schussler et al 1996;Gourley et al 2003). We were not able to find IREs in organisms outside the metazoan group.…”
Section: Ferritinsupporting
confidence: 80%
“…The only metazoan species where we failed to identify an IRE were Caenorhabditis elegans and Schistosoma mansoni, consistent with previous observations (Schussler et al 1996;Gourley et al 2003). We were not able to find IREs in organisms outside the metazoan group.…”
Section: Ferritinsupporting
confidence: 80%
“…Sequence analysis showed that Hlfer2 mRNA lacks an IRE, similar to the secretory ferritin of I. ricinus (Hajdusek et al, 2009), the yolk ferritin of L. stagnalis (von Darl et al, 1994), S. mansoni ferritins (Schüssler et al, 1996) and Haliotis discus discus Abf1 (De Zoysa and Lee, 2007). In contrast to HlFER1, HlFER2 contains a signal peptide and was detected in the hemolymph using a specific antiserum.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, transcriptional regulation of ferritin is most frequently (although not universally) identified as a primary mode of response to exogenous iron as well as stress-related signals. [65][66][67][68][69][70][71][72] …”
Section: Ferritin Genes and Mutationsmentioning
confidence: 99%